The redistributive effects of a money-financed fiscal stimulus - Chiara Punzo; Lorenza Rossi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
This paper analyzes the redistributive channel of a money financed fiscal stimulus (MFFS). It shows that the way in which this regime is implemented is crucial to determine its redistributive effects and consequently its effectiveness. In normal times, the most effective regime is a MFFS with no additional intervention by the Central Bank to stabilize the real public debt using inflation, whereas a MFFS accompanied by real debt stabilization - through the adjustment of seigniorage - is the most effective one in a ZLB scenario. In a TANK model this regime is so effective to avoid the recessionary effects implied by the ZLB. This result does not hold in a RANK model, where the redistributive channel is absent. Remarkably, contrary to the common wisdom a MFFS is followed by a moderate increase of inflation, which is only temporarily higher than the target.
Keywords: E32; E52; E62; 330; Money-Financed fiscal stimulus; seignorage; government spending; redistribution; borrower-saver; fiscal multipliers; welfare; RANK versus TANK